The impact of the COVID-19 pandemic on the quantity and quality of sleep in medical university students - Karolina Rogacka; Bartłomiej Pyrak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2022)
Introduction: In order to overpower COVID-19 pandemic a number of security measures have been taken, including limiting of leaving people's place of residence, which is associated with increased social isolation. For students an additional change resulting from the current epidemiological situation is the transition to remote learning which is related with increased time spent in front of a computer or smartphone screen. The aim of the study: The aim of the study was to determine whether the COVID-19 pandemic affects the quality and quantity of sleep in a group of medical students. Materials and methods: Survey search using author-made questionnaire was conducted. Questionnaire included questions about quality and quantity of sleep before and after COVID-19 pandemic outbreak. Collected data was then transformed for statistical purposes and the correlations were examined using Wilcoxon test (before vs after pandemic) or Mann-Whitney U-test (men vs women). Results: Comparing the situation before the pandemic to the present one, statistically significant increase in difficulty in falling asleep in the study group was observed (p=0,008). A statistically significant sleep duration was observed (the mean increased from 7,09 to 7,53, p<<0.05). Students also go to bed later (p<<0.05) and wake up later (p<<0.05). Students also complained about waking up more frequently at night (p=0,006). The respondents rate their current sleep quality worse than before the pandemic (p=0,039). Conclusions: Sleep quality in the group of medical students deteriorated during the pandemic, while the amount of sleep increased. Since the introduction of remote learning, the time of using electronic devices has significantly increased. The obtained results may be used for further research on the impact of the COVID-19 pandemic and remote learning on the quality and quantity of sleep